Study on the influence of rapid stretching compound training on the physical fitness of police officers - Yun Chen (Quality in Sport)
The purpose of this study was to systematically evaluate the effects of Plyometric Training on the physical fitness of police officers, and to verify it using a rigorous randomized controlled experimental design. In this study, 40 police officers from a police college were randomly divided into experimental group and control group, 20 in each group. The experimental group received the rapid stretching compound training intervention, while the control group maintained the traditional training mode. The experiment period was 8 weeks, training 3 times a week, 60min each time. In this study, key physical indicators such as 50-meter running, grip strength, standing long jump, and 10-meter ×4 round trip running were used for intervention, and the training effects were evaluated before and after. The results showed that the experimental group was significantly better than the control group in the improvement of speed, explosive power and sensitivity, with statistical significance (P<0.05), only the improvement of maximum grip strength did not reach a significant level. Rapid stretching compound training is of great value in improving the sports performance of police officers, especially in the police tasks requiring short time high intensity explosive power and sensitivity.